5x-4=(2x+5)×2解方程5x-4=(2x+5)×26分之x-29+3分之9+3x还有这几题1、6分之x-29+3分之9+3x=352、3x+4x+6分之5=12分之10+7x+86+2-103、4*(x-2)+20x=3004、1-2(x-6分之1)=3分之1
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 15:44:52
5x-4=(2x+5)×2解方程5x-4=(2x+5)×26分之x-29+3分之9+3x还有这几题1、6分之x-29+3分之9+3x=352、3x+4x+6分之5=12分之10+7x+86+2-103
5x-4=(2x+5)×2解方程5x-4=(2x+5)×26分之x-29+3分之9+3x还有这几题1、6分之x-29+3分之9+3x=352、3x+4x+6分之5=12分之10+7x+86+2-103、4*(x-2)+20x=3004、1-2(x-6分之1)=3分之1
5x-4=(2x+5)×2解方程
5x-4=(2x+5)×2
6分之x-29+3分之9+3x
还有这几题
1、6分之x-29+3分之9+3x=35
2、3x+4x+6分之5=12分之10+7x+86+2-10
3、4*(x-2)+20x=300
4、1-2(x-6分之1)=3分之1
5x-4=(2x+5)×2解方程5x-4=(2x+5)×26分之x-29+3分之9+3x还有这几题1、6分之x-29+3分之9+3x=352、3x+4x+6分之5=12分之10+7x+86+2-103、4*(x-2)+20x=3004、1-2(x-6分之1)=3分之1
(1):
5x-4=(2x+5)×2
5x-4=4x+10
x=14
(2):
(x-29)/6+(9+3x)/3
=[(x-29)+2(9+3x)]/6
=(x-29+18+6x)/6
=(7x-11)/6
5x-4=(2x+5)×2
x=14
5x-4=(2x+5)×2
5x-4=4x+10
5x-4x=10+4
x=14
5x-4=4x+10
5x-4x=10+4
x=14
16又3分之7
5x-4=(2x+5)×2
5X-4=4X+10
5X-4X=10+4
X=14
6分之x-29+3分之9+3x这不是方程
解方程;x/x-4=5x/x-2
5x(x+7)(x+4)=5x(x^2+11X)解方程,
解方程 x(2x-4)+3x(x-1)=5x(x-3)+8
解方程:x(3x-4)+2x(x+7)=5x(x-7)+90
解方程:(x+3)/(x+2)-(x+4)/(x+3)=(x+5)/(x+4)-(x+2)/(x+1)
解方程 x+2/x+1+x+8/x+7=x+6/x+5+x+4/x+3
解方程:2x+4x+6x...+100x=1-(x+3x+5x+...+99x)
解方程(x-2)/(x-3)-(x-3)/(x-4)=(x-5)/(x-6)-(x-6)/(x-7)
解方程 (x+2)/(x+1) - (x+4)/(x+3)=(x+6)/(x+5)-(x+8)/(x+7)
解方程(x+4)(x-5)=x^2-20
解分式方程:4/5x+x/(5x-25)=5/(x^2-5x)
解方程 x^2(3x+5)+5=x(-x^2+4x^2+5x)+x
解方程5/(x^-2x)-4/(x^2+2x)=3/x^2-4
解方程:(x+5)(x-4)+(4-x)^2-(x-4)(2x-7)=16
解方程:(4/x-2)+(x-1/x-5x+6)+(2/3-x)=0
解方程x(2x-3)+3x+3x(x-2)=5x(x-4)+11
7x(x-6)+3x=4x(2x+5)怎么解这个方程
(x-3)(x+8)=(x+4)(x-7)+2(x+5)解方程,